Nutritional knowledge and behaviours among adolescents in Calabar: Towards prevention of diet-related noncommunicable diseases - Danjuma DS; Odiba EE; Fele VO; Onyenweaku EO (Ibom Medical Journal, 2025)
Background: Non-communicable diseases (NCDs) such as cardiovascular diseases, diabetes, cancer, and obesity are major global health concerns currently. Adolescents are also increasingly exposed to NCD risk factors due to poor dietary habits and lifestyle choices that they are exposed to during this formative period. These unhealthy dietary and lifestyle habits include low fruit and vegetable consumption, frequent intake of sugary, highly processed foods and physical inactivity.